Incidencia de falsos positivos por COVID-19, mediante determinación de Proteína C Reactiva - Kevin Daniel, Carrillo Bravo (2020)
Introduction: Pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection arose in Wuhan city, Hubei province, China, in December 2019. Objectives: The incidence of false positives by the C-reactive protein test in patients suspected of COVID-19 of Carlos Andrade Marín Hospital, during May - June 2020. Material and methods: This study will use a descriptive, observational, retrospective cross-sectional method by which treated patients in the Emergency area with a presumptive diagnosis of COVID-19, including a sample of 287 cases. Results: In those who underwent a C-reactive protein test and nasal swab, 163 had a positive effect for both tests representing 57% of the population; 26 patients had a positive PCR result with a negative nasal swab representing 9% of false positives. Conclusions: The incidence of false positives by determination of C-reactive protein at Hospital Carlos Andrade Marín in the geriatric population was 9%, compared to 57% of the people that had a positive result for PCR test and nasal swab, is a relatively low but not insignificant value, which shows that although false positives can occur by PCR, it is necessary to take into account more parameters to make the diagnosis of COVID-19 in addition to the results of laboratory tests.